PELAKSANAAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Anggreni Sy, Devi; Fitriyani, Fitriyani (LPPM Universitas Bina Insan, 2020)
This study discusses the implementation of Law No. 23, 2004 concerning the Elimination of Domestic Violence, raising problems and obstacles in the implementation of the implementation of the Law. The research objective is to explore the principles and systematics of law, especially those concerned with criminology against crimes committed within the scope of the household, the research carried out is classified as exploratory sociological legal research. The method used in data collection using library research (library research) to obtain secondary data and field research (field research) to obtain primary data by looking for data directly from the community conducting interviews. Data processing techniques are carried out by analyzing and constructing in a conclusion that the implementation of Law No. 23, 2004 concerning the Elimination of Domestic Violence has not been fully implemented properly and effectively. Obstacles in the Implementation of Law No. 23, 2004 concerning the Elimination of Domestic Violence are the victims and the community itself.